Spin Coated Gallium Oxide Thin Films And The Effect Of Mo-Doping Concentration On Luminescence Properties - Wang, Tiankun (2023)
Beta-type gallium oxide (β-Ga2O3) with ultra-wide band gap energy and good emission property is suitable for optoelectronic applications such as luminescence devices. However, the growth of good quality β-Ga2O3 films using low cost and simple techniques, particularly the sol-gel spin coating technique, is still remains challenging. For luminescence features, undoped and doped β-Ga2O3 emit multicolour emissions due to the multi-energy level of intrinsic vacancies, which is unsuitable for the display application. From the fundamental and engineering point of view, it is worth investigating the above topics. In this project, the β-Ga2O3 thin films synthesized by the sol-gel spin coating method and their photoluminescence were investigated. For the fabrication, the sol-gel spin coating growth conditions, and processes of the β-Ga2O3 thin films on Si and Al2O3 substrates were investigated. Special treatments on the substrate and the coated layer were conducted to improve the uniformity and smoothness of each coated layer and the final deposited film. Different spin coating cycles, and annealing temperatures were also investigated from the morphologic and optical aspects. Finally, a set of samples with 6-layers spin-coated films and annealed under different temperatures, i.e., from 900 °C, to 1100 °C were prepared. These samples were then subjected to an in-depth X-ray diffraction analysis. The results show that the micro strain is not the key factor for the Bragg peaks broadening. To investigate luminescence properties, a series of Mo-doped β-Ga2O3 on Al2O3 were synthesized. A green luminescence band associated with the Mo ion dxz-dyz band transition appeared slowly with the increase of the Mo-doping concentration.